2018
DOI: 10.1007/s00709-018-1303-4
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis tonoplast intrinsic protein and vacuolar H+-adenosinetriphosphatase reflect vacuole dynamics during development of syncytia induced by the beet cyst nematode Heterodera schachtii

Abstract: Plant parasitic cyst nematodes induce specific hypermetabolic syncytial nurse cell structures in host roots. A characteristic feature of syncytia is the lack of the central vacuole and the formation of numerous small and larger vesicles. We show that these structures are formed de novo via widening of ER cisternae during the entire development of syncytium, whereas in advanced stages of syncytium development, larger vacuoles are also formed via fusion of vesicles/tubules surrounding organelle-free pre-vacuole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…However, the fact that we observed fluorescently labelled spherical structures with VPE activity close to the nematode’s head and in the apical region of the growing syncytia at 7 and 14 dpi cannot be ignored. Similar structures were observed by Baranowski et al () in syncytia induced by H. schachtii in A. thaliana roots. Some of these were considered to be lytic vacuoles and our results confirm these observations because the activity of legumains is inseparably associated with lytic vacuoles.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the fact that we observed fluorescently labelled spherical structures with VPE activity close to the nematode’s head and in the apical region of the growing syncytia at 7 and 14 dpi cannot be ignored. Similar structures were observed by Baranowski et al () in syncytia induced by H. schachtii in A. thaliana roots. Some of these were considered to be lytic vacuoles and our results confirm these observations because the activity of legumains is inseparably associated with lytic vacuoles.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, VPEs are considered as initiators of the vacuolar protein processing machinery (Hatsugai et al , ). Moreover, recently it has been shown that the organization of the vacuolar system in the syncytium induced by the beet cyst nematode H. schachtii in Arabidopsis thaliana roots changes dynamically during syncytium development, which indicates the importance of this cell compartment during plant–nematode interactions (Baranowski et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Caution is even more justified when subsequent regulatory levels are taken into account, e.g., post-translational modifications, subcellular localization, or substrate availability. In addition, the substantial number of detected proteome components involved in protein degradation, biosynthesis, and cellular trafficking processes supports not only the known enhancement of metabolic activity of syncytia, but also more recent findings on the role of autophagy and organellar de novo biogenesis during plant-nematode interactions [15,45].…”
Section: Discussionsupporting
confidence: 55%
“…Tonoplast intrinsic proteins (TIPs), localised in vacuoles, play a key role in plant defences against PPNs through the regulation of water and ion transport ( Baranowski et al, 2019 ). Therefore, three TIP genes ( TIP1.1 , TIP1.2 , TIP1.3 ), which displayed significant downregulation in the RKN-infected susceptible tomato roots ( Shukla et al, 2018 ), were selected to study the effects of Bv-DS 1 on their expression in the RKN-inoculated tomato roots.…”
Section: Resultsmentioning
confidence: 99%
“…The tonoplast intrinsic proteins (TIPs) have been described as the most abundant aquaporin proteins localized in the plant tonoplast ( Maurel et al, 2009 ) and play an important role in plant growth and development by regulating the transport of small substrates, such as water, glycerol, ammonia, H 2 O 2 , and urea ( Höfte et al, 1992 ; Gerbeau et al, 1999 ; Soto et al, 2008 ; Lindahl et al, 2018 ). TIPs have also been found to regulate plant responses to PPN infection ( Szakasits et al, 2009 ; Xue et al, 2013 ; Baranowski et al, 2019 ). In Arabidopsis , the feeding-site (syncytia) formation by cyst nematode is accompanied by reduced expression of several TIP genes ( Szakasits et al, 2009 ; Baranowski et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%